Incidence of cancer-associated thromboembolism in Japanese gastric and colorectal cancer patients receiving chemotherapy: a single-institutional retrospective cohort analysis (Sapporo CAT study) - Naoya Sakamoto; Ayane Oba Aonuma; Michio Nakamura; Kentaro Sakamaki; Taichi Murai; Chika Matsuda; Kazufumi Itaya; Takayuki Sone; Masataka Yagisawa; Yuta Koike; Ayana Endo; Yoko Tsukuda; et al. (BMJ Open)
Objective Few data regarding the incidence of cancer-associated thromboembolism (TE) are available for Asian populations. We investigated the incidence of TE (TEi) and its risk factors among gastric and colorectal cancer (GCC) patients received chemotherapy in a daily practice setting.Design A retrospective cohort study.Setting A single-institutional study that used data from Sapporo City General Hospital, Japan, on patients treated between January 2008 and May 2015.Participants Five hundred Japanese GCC patients who started chemotherapy from January 2008 to May 2015.Primary and secondary outcome measures TE was diagnosed by reviewing all the reports of contrast-enhanced CT performed during the follow-up period. All types of thrombosis detected by CT or additional imaging tests, such as venous TE, arterial TE and cerebral infarction, were defined as TE. Medical records of all identified patients were reviewed and potential risk factors for TE, including clinicopathological backgrounds, were collected. We defined the following patients as ‘active cancer’; patients with unresectable advanced GCC, cancer recurrence during or after completing adjuvant chemotherapy and/or presence of other malignant tumours.Results Of the 500 patients, 70 patients (14.0%) developed TE during the follow-up period. TEi was 9.2% and 17.3% in GCC patients, 18.1% and 3.5% in active and non-active cancer patients, and 24.0% and 12.9% in multiple and single primary, respectively. Multivariate logistic regression analysis showed that colorectal cancer (CRC) (OR 2.371; 95% CI 1.328 to 4.233), active cancer (OR 7.593; 95% CI 2.950 to 19.543) and multiple primary (OR 2.527; 95% CI 1.189 to 5.370) were independently associated with TEi.Conclusion TEi was 14.0% among Japanese GCC patients received chemotherapy, and was significantly higher among patients with CRC, active cancer and multiple primary than among those with gastric cancer, non-active cancer and single primary, respectively.Trial registration number UMIN000018912.